2014
DOI: 10.1212/01.wnl.0000451931.25063.e5
|View full text |Cite
|
Sign up to set email alerts
|

Gait speed in Parkinson disease correlates with cholinergic degeneration

Abstract: et al. 1 attempted to establish an association between glucose metabolism and memory performance. They concluded that higher blood glucose levels negatively influenced cognition. We believe that the design and methodology is inadequate to draw these conclusions.The bivariate approaches do not consider that confounding factors might be related to both glucose metabolism and memory (e.g., age). The hippocampus as a potential mediator is stated to lose significance upon adjustment for even the most basic confound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…We think that our data are noteworthy for physicians, physiotherapists, and researchers. The walking speed of patients with Parkinson's disease has been shown to be related with age, disease severity, and balance in the literature (28,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…We think that our data are noteworthy for physicians, physiotherapists, and researchers. The walking speed of patients with Parkinson's disease has been shown to be related with age, disease severity, and balance in the literature (28,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Non-motor symptoms may eventually become chief complaints and therapeutic challenges in advanced stages of PD. Nonetheless, studies have shown that some motor symptoms observed in PD, like postural instability and walking/gait problems, are mostly secondary to degeneration of non-dopaminergic pathways and significantly contribute to impairment and disability in advanced PD patients [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%